Greek derivational affixes roots or categorizers? - Alexiadou, Artemis (Linguística: Revista de Estudos Linguísticos da Universidade do Porto, 2021)
In this paper, I am concerned with the status of derivational affixes in Distributed Morphology: are these roots or categorizers? I will compare Greek to English and Dutch, as some derivational affixes in these two languages have been claimed to be roots. I will show that Greek derivational affixes are categorizers, and I will offer an explanation that capitalizes on the stress properties of Greek derivational affixes.